2018
DOI: 10.1213/ane.0000000000002341
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Nasal Cannula Can Either Impair or Enhance Preoxygenation With a Bag Valve Mask: A Randomized Crossover Design Study Comparing Oxygen Flow Rates

Abstract: Our study found that NC at 0 and 5 lpm with a BVM is deleterious to preoxygenation and should be avoided. In addition, a lack of difference between NC-10 and BVM-only demonstrates that NC at flows of at least 10 lpm should not impair the preoxygenation process. While NC-15 may offer a benefit by reaching maximal ETO2 at 1 minute, this would need to be balanced against patient comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The patients' SpO 2 has never been lower than 91%. After using HFNC, it is expected to extend the apnea time, but in this process, carbon dioxide level monitoring is required [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients' SpO 2 has never been lower than 91%. After using HFNC, it is expected to extend the apnea time, but in this process, carbon dioxide level monitoring is required [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the optimal strategy for preoxygenation, but so far these have only been completed on healthy volunteers or stable patients in the OR. [16][17][18][19][20][21][22][23] Given clinicians used the BVM in nearly 90% of patients in the study group our results suggest that utilizing a BVM allows a good mask seal and real-time feedback with ETO 2 monitoring, which may therefore lead to better preoxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…[24] McQuade et al found an increase in end tidal oxygenation (EtO2) with NC at rates >15 LPM, deleterious effect with <5LPM, and no benefit when an adequate seal was achieved with BVM alone, as the addition of NC disrupted the mask seal, potentially explaining the study results by Caputo. [29] Yet, in cases of with a mask leak, there was benefit from adding the nasal cannula. [29] Russotto found that apneic oxygenation with low flow or high flow nasal cannula decreased desaturation.…”
Section: Apneic Oxygenationmentioning
confidence: 99%
“…[29] Yet, in cases of with a mask leak, there was benefit from adding the nasal cannula. [29] Russotto found that apneic oxygenation with low flow or high flow nasal cannula decreased desaturation. [16] A 2016 study by Sakles and Mosier et al demonstrated increased first pass success without hypoxia in patients with apneic oxygenation, though it should be noted that these patients were primarily intubated for airway protection and traumatic injuries.…”
Section: Apneic Oxygenationmentioning
confidence: 99%